Collaborative Case Review: A Systems-Based Approach to Patient Safety Event Investigation and Analysis. Issue 2 (8th March 2022) - Lacson, Ronilda; Khorasani, Ramin; Fiumara, Karen; Kapoor, Neena; Curley, Patrick; Boland, Giles W.; Eappen, Sunil
Abstract : Objectives: The aims of the study were to assess a system-based approach to event investigation and analysis—collaborative case reviews (CCRs)—and to measure impact of clinical specialty on strength of action items prescribed. Methods: A fully integrated CCR process, co-led by radiology and an institutional patient safety program, was implemented on November 1, 2017, at our large academic medical center for evaluating adverse events involving radiology. Quality and safety teams performed reviews for events identified with other departments who maintained their existing processes. This institutional review board–approved study describes the program, including percentage of CCR from an institutional Electronic Safety Reporting System, percentage of CCR per specialty, and action item completion rates and strength (e.g., stronger) based on a Veterans Administration–designed hierarchy. χ 2 analysis assessed impact of clinical specialty on strength of action prescribed. Results: Seventy-three CCR in 2018 generated 260 action items from 10 specialties. Seventy percent (51/73) were adverse events identified through Electronic Safety Reporting System. The specialty most frequently associated with CCR was radiology (16/73, 22%). Most action items (204/260, 78%) were completed in 1 year; stronger action items were completed in 71 (27%) of 260. Radiology was responsible for 61 action items; 25 (41%) of 61 were strong versus all other specialties with strong action items in 46 (23%) of 199 ( P < 0.01). Conclusions: An integrated multispecialty CCR co-led by the radiology department and an institutional patient safety program was associated with a higher proportion of CCR, stronger action items, and higher action item completion rate versus other hospital departments. Active engagement in CCR can provide insights into addressing adverse events and promote patient safety.